نشاط مكتب منظمة التحرير الفلسطينية بتونس 1982 -1993م - عبد الحكيم بوغزالة حمد; حسام حمصي (University of Eloued جامعة الوادي, 2025)
"ملخص: عنوان المذكرة بالعربية: "" نشاط مكتب منظمة التحرير الفلسطينية بتونس 1982 – 1993م"" يُعد موضوع منظمة التحرير الفلسطينية من المواضيع البالغة الأهمية والتعقيد على المستويين العربي والدولي، نظراً لما يحمله من أبعاد سياسية وتاريخية متشابكة. وتُسلّط هذه الدراسة الضوء على مرحلة محورية في مسيرة النضال الفلسطيني، تمثلت في انتقال منظمة التحرير من لبنان إلى تونس واستقرارها بها خلال الفترة الممتدة من 1982 إلى 1993م، وهي المرحلة التي شهدت تحولًا جوهريًا في استراتيجيتها الكفاحية ضد الاحتلال الصهيوني. فقد أملَت الظروف الإقليمية والدولية المحيطة بالمنظمة خلال تلك المرحلة، تبنّي نهج سياسي جديد قادها إلى قبول مبادرات التسوية والدخول في مسار المفاوضات، ما أسفر في نهاية المطاف عن تحول المنظمة من حركة تحرر وطني إلى سلطة فلسطينية تمارس مهامها في أجزاء من الضفة الغربية وقطاع غزة، مع الإقرار بإسرائيل كدولة مجاورة. " Summary: - Thesis Title in English : ""the Activity of the Palestine Liberation Organization Office in Tunisia (1982–1993)"" The topic of the Palestine Liberation Organization (PLO) holds significant importance and complexity on both the Arab and international levels, due to its deeply intertwined political and historical dimensions. This study sheds light on a pivotal phase in the Palestinian national struggle, marked by the relocation of the PLO from Lebanon to Tunisia and its establishment there between 1982 and 1993. This period witnessed a fundamental transformation in the organization’s strategy of resistance against the Zionist occupation. The regional and international circumstances surrounding the PLO during this time compelled it to adopt a new political approach, leading to its acceptance of peace initiatives and engagement in negotiation processes. Ultimately, this shift resulted in the organization’s transformation from a national liberation movement into a Palestinian Authority administering parts of the West Bank and Gaza Strip, while recognizing Israel as a neighboring state.
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: حركة تحرر وطني; النضال الفلسطيني; منظمة التحرير الفلسطينية; Palestine Liberation Organization (PLO); Palestinian Struggle; National Liberation Movement